Green Marketing and Intention to Mantain Sustainable : Case Study On Rural Tourism In Malang - Mega Mirasaputri Cahyanti; Dan William Menanti (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
The negative impact of aggressive marketing on tourism destinations in Indonesia become a main concern to various groups. Whereas, the purpose of developing rural tourism is not only to achieve economic sustainability but also to sustain environment. The concept of green marketing is estimated to be a worthy solution to maintain the sustainability of tourism destination. Therefore, this study aims to determine the effect of green marketing concept to affect tourists's intention for avoiding the damage in the future of new rural tourism. Meanwhile, some methods used in this research and the type of this research were descriptive research. Sampling technique used in this research was incidental purposive sampling and the sample was tourists on rural tourism like in “Kampung Wisata in Malang” with the number of the sample was 200 tourists. Analysis technique used Partial Least Square (PLS) analysis. The result of this research was Green Marketing has a positive and significant effects on the tourists’s intention to maintain the sustainability of rural tourisms. Physical evidence and products as well as promotions and prices are indicators of green marketing that must be considered more.